Challenges of monocyte HLA-DR targeted immunomodulation in sepsis—a prospective observational cohort study - Snow, Timothy Arthur Chandos; Villa, Antoine; Cesar, Antonio; Ryckaert, Francis; Saleem, Naveed; Smyth, Deborah; Pan, Holly; Flint, Julia; Brealey, David; Singer, Mervyn; Gilroy, Derek W.; Arulkumaran, Nishkantha; et al. (Frontiers in Immunology, 2026)
IntroductionReduced monocyte HLA-DR expression, a hallmark of immunosuppression in sepsis, is associated with infectious complications and mortality. Therapeutic strategies, including IFN-γ, have been used to restore monocyte HLA-DR and immune function, but have not consistently improved clinical outcomes. Therefore, we conducted an iterative series of experiments to re-examine the core assumptions and address the key gaps in the current understanding.MethodsWe conducted a prospective cohort study of patients admitted to the intensive care unit (ICU) with sepsis (n = 55, 36% mortality) to characterize the dynamics of monocyte HLA-DR expression and associated functional pathways. Flow cytometry was used to evaluate monocyte phenotype, and lipopolysaccharide (LPS) stimulation was used to assess monocyte functional capacity. We examined canonical monocyte pathways and identified those that were responsive to LPS stimulation and/or modulated by IFN-γ ex vivo. We evaluated monocyte HLA-DR expression in the peripheral blood and inflamed tissues of healthy volunteers following intradermal administration of UV-killed E. coli.ResultsMonocyte HLA-DR expression was significantly lower in patients than in healthy volunteers, particularly in non-survivors. Monocyte phenotypes evolved discordantly over time, some markers trended toward healthy levels, while others diverged, with no consistent distinction between survivors and non-survivors. Intracellular trafficking of membrane HLA-DR on bacterial phagocytosis contributes to the reduced surface HLA-DR expression. Compared to healthy volunteers, monocytes from ICU patients had a significantly lower expression of proteins associated with antigen presentation and co-stimulation, cytokines, phagocytosis, and a blunted response to LPS. IFN-γ increased the levels of proteins involved in antigen presentation, but their expression remained significantly lower than that in healthy controls. Healthy volunteers demonstrated compartment-specific and temporally distinct regulation of monocyte HLA-DR in circulation versus that in inflamed tissue.ConclusionReduced monocyte HLA-DR expression in sepsis reflects broad disruptions across multiple pathways, explaining the limited efficacy of therapeutic interventions. Further insights into the mechanisms governing therapeutic modulation of monocyte HLA-DR and immune function are required to identify patients who are most likely to benefit from intervention.